Separation and cleaning of Leymus chinensis seed threshing material based on gas-solid coupling - Ma, Zongyu; Wan, Qihao; Liu, Weiwei; Zhang, Yingzhong; Bu, Ku; Du, Wenliang (International Journal of Agricultural and Biological Engineering, 2023)
The aim of this study was to improve the cleaning performance of the Leymus chinensis seed threshing material separation and cleaning device, and to clarify the movement law and characteristics of the Leymus chinensis seed threshing material during the cleaning process. A numerical simulation of the separation and cleaning process of Leymus chinensis seed threshing material was performed using the computational fluid dynamics¬ discrete element approach. According to the streamline distribution of the gas-solid coupling, the movement of Leymus chinensis seeds during the cleaning process was examined. Additionally, the average speed and quantity of Leymus chinensis seed threshing material in different separation and cleaning zones were studied over time. Meanwhile, the distribution principle of the threshing material was obtained, and a verification test of the under-sieve distribution was conducted. The test results showed that the numerical simulation was consistent with the distribution trend of the under-sieve. The cleaning performance verification test showed that the impurity content and the loss rate of the separation and cleaning device were 27.3% and 3.3%, where the test results, compared with those of the numerical simulation, showed a reduction of 1.5% and 0.8%, respectively. It is feasible to apply the theory and method of gas-solid coupling to simulate the separation and cleaning process of Leymus chinensis seeds.Keywords:cleaning performance, gas-solid coupling, Leymus chinensis seeds, numerical simulation, separation and cleaningDOI: 10.25165/j.ijabe.20231605.8140Citation: Ma Z Y, Wan Q H, Liu W W, Zhang Y Z, Bu K, Du W L, et al. Separation and cleaning of Leymus chinensis seed threshing material based on gas-solid coupling. Int J Agric & Biol Eng, 2023; 16(5): 283–290.